Preparation method of spherical calcium carbonate particles
Through the spray drying process and the use of crystal form control agent, the problem of the difficulty in stably preparing spherical calcite structure nanocalcium carbonate particles in the prior art is solved, and stable spherical particles preparation and application performance are improved.
Patent Information
- Application Number
- CN202510336671.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-21
AI Technical Summary
It is difficult to stabilize the preparation of nano calcium carbonate particles with spherical calcite structures in the prior art, resulting in a high proportion of calcite particles, affecting their application performance.
Spherical calcium carbonate particles are directly prepared by spray drying. The nanoparticles have high surface tension and are prone to hard agglomeration to generate spherical nanocalcium carbonate particles. The morphology and structure of the particles are controlled by regulating process conditions and adding crystal form control agents.
A stable spherical calcite structure nano-calcite calcium carbonate particles is achieved, which reduces the proportion of calcite particles, improves the application performance of nano-calcite calcium carbonate, and significantly improves the mechanical properties of polyethylene films.
Smart Images

Figure CN119858935A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing nano calcium carbonate particles, in particular to a method for preparing nano spherical calcium carbonate particles. Background Art
[0002] Calcium carbonate is a commonly used inorganic filler, and its size and shape vary depending on the application field. Calcium carbonate is generally common in rhombohedral, rod-shaped, needle-shaped, and spindle-shaped forms, and its crystal structure is generally a calcite structure. Nano calcium carbonate is an ultrafine solid powder material that emerged in the 1980s. Because nano calcium carbonate particles are ultrafine, their crystal structure and surface electronic structure produce quantum size effects and surface effects that ordinary calcium carbonate does not have, making it play a role in strengthening and toughening in many application fields such as rubber, plastics, papermaking, coatings, adhesives, and inks. However, due to its generally high viscosity, its processing performance is restricted.
[0003] Carbonization is a common method for chemical preparation of nano calcium carbonate. The main process is to first calcine limestone to obtain quicklime and carbon dioxide. The quicklime is digested and reacted with water to obtain calcium hydroxide slurry. Purified carbon dioxide is then introduced into the calcium hydroxide slurry to obtain calcium carbonate slurry. After dehydration and drying, the nano calcium carbonate product is obtained. Carbonization reaction is the most critical process step in the production process of nano calcium carbonate. The control of reaction conditions determines the particle size and distribution of the product. Improper operation of the drying process can easily lead to agglomeration and compaction of nano calcium carbonate. Unfortunately, the current nano calcium carbonate carbonization and drying equipment has many and demanding process parameters to control, so it is difficult to stably control product quality, which seriously restricts the application and development of nano calcium carbonate.
[0004] On the other hand, spherical calcium carbonate has the characteristics of large filling volume and low system viscosity, so it is the research object of people's attention, but it is usually a vaterite structure, so its structure itself is not very stable. If the process is designed according to the preparation of vaterite calcium carbonate, it is very likely that there will be a large proportion of calcite crystal nano calcium carbonate particles in the end.
[0005] Generally, calcium carbonate with vaterite structure is synthesized by double decomposition method, and spherical particles are formed by adding additives. The structure is mostly vaterite structure, which is a metastable structure and can be easily transformed into calcite structure. However, since pure calcite crystal form is very suitable for crystal growth, the crystal will quickly grow into calcite particles with larger particle size, which is not conducive to the preparation of nano calcium carbonate.
[0006] Therefore, how to prepare nano-CaCO3 products with different morphological characteristics and special functions by adjusting different process conditions and adding different crystal control agents, so as to improve its application performance in this industry and expand its use value, is the focus of current research.
[0007] For example, Chinese patent document CN202211027646.X discloses a surface-modified nano-calcium carbonate and a preparation method thereof, the steps comprising: (1) preparation of a crystal form control agent: the crystal form control agent comprises a solution A and a solution B, the solution A is an aqueous solution of zinc gluconate, and the solution B is a protein composite solution; (2) preparation of nano-calcium carbonate; (3) modification of nano-calcium carbonate: surface modification of nano-calcium carbonate is performed using a composite aqueous solution of KH550 and sodium stearate to obtain modified nano-calcium carbonate. The prepared nano-calcium carbonate has a large specific surface area, and after being added to a polyethylene film, the mechanical properties are improved to a certain extent, but still need to be further improved.
[0008] However, there is an urgent need in the prior art for a technical solution to stabilize the calcite structure of nano-calcium carbonate particles before growing into calcite particles. Summary of the invention
[0009] In order to solve the problem that it is difficult to obtain stable calcite structured spherical calcium carbonate particles and reduce the proportion of calcite particles in the prior art, the present invention provides a set of technical solutions for preparing spherical calcium carbonate particles.
[0010] Specifically, according to the first aspect of the present invention, a method for preparing spherical calcium carbonate particles by using a spray drying process is provided. After preparing synthetic nano-scale calcium carbonate particles by using a lime milk carbonization method, no surface treatment or surface coating is performed, but instead a spray drying method is used to directly perform spray drying, thereby generating spherical nano calcium carbonate particles by utilizing the characteristics of nanoparticles having large surface tension and being easy to produce hard agglomerates.
[0011] According to the above-mentioned method for preparing spherical calcium carbonate particles by using a spray drying process, the following equipment for preparing spherical calcium carbonate particles is used, including a lime milk temperature-controlled carbonization reactor device, a venturi tube processing device, and a spray drying device; the lime milk temperature-controlled carbonization reactor device includes a carbonization reactor, a cooling component on the outer layer of the reactor, and a cooling coil is arranged on the inner layer, the cooling component and the cooling coil are connected to a coolant storage tank through a liquid cooling pipeline, and the coolant storage tank is connected to a refrigeration device; the bottom of the carbonization reactor is connected to the venturi tube processing device through a pipeline; the spray drying device is connected to the calcium carbonate clinker agglomerated after being treated by the venturi tube processing device through a pipeline via a clinker slurry pump.
[0012] Furthermore, a slurry feed port, a stirring motor, a plurality of temperature sensors and a pH test box are arranged on the top of the carbonization reactor; a hollow stirring rod with a paddle is arranged at the center of the carbonization reactor, and carbon dioxide gas is passed through the inside of the stirring rod.
[0013] Furthermore, a rotating ultrasonic atomizing nozzle is provided at the bottom of the stirring rod.
[0014] Furthermore, the venturi tube treatment device includes a gas-liquid dual-phase dual-channel venturi tube, a heating device and a cooling device. The cooled carbon dioxide gas is discharged from the gas discharge port or collected for other uses, and the cooled cooked slurry is sent to the spray drying device, which includes a spray drying growth tower, a spray nozzle, an air intake fan, an air heating device, a separator, a fan and a dust collector; a spray nozzle is arranged in the inner cavity of the spray drying growth tower, and the spray nozzle is connected to the cooked slurry pump, and the spray drying reaction tower is also connected to the separator, and the separator is connected to the dust collector through a fan and a pipeline.
[0015] Furthermore, in the temperature-controlled carbonization reactor, the raw material slurry is pumped into the carbonization reactor from the feed port, and when the stirring motor drives the stirring rod with paddles to stir, the carbon dioxide enters the carbonization reactor from the rotating ultrasonic atomizing nozzle via the stirring rod to react with the raw material slurry for carbonization reaction; the heat generated by the carbonization reaction is cooled by the coolant through the cooling coil and the cooling component heat exchange, and the coolant absorbs the heat of the carbonization reaction system and enters the coolant storage tank, and is cooled by the refrigerator and then returns to the coolant storage tank, and is pumped into the cooling coil and the cooling component by the refrigerant pump again to exchange heat with the carbonization reaction system; the temperature and pH value of the slurry in the carbonization tank are monitored by the temperature sensor and the pH test box. When the pH value drops to a certain value, the reaction is stopped, and the slurry is connected to the Venturi tube treatment device after stirring for a period of time. In the spray drying device, the clinker slurry is pumped out from the cooling device in the venturi tube processing device by the clinker slurry pump and enters the interior of the spray drying generating tower through the spray nozzle, and the air is sucked into the spray drying generating tower by the air intake fan through the air heating device; the dried nano calcium carbonate material is discharged from the material discharge port at the bottom of the spray drying tower, and the carbon dioxide gas is separated from the material by the separator and discharged into the atmosphere after passing through the fan and the dust collector.
[0016] In view of the problem that the heat released by the carbonization reaction causes the temperature of the carbonization reaction system to rise, and the reaction speed is accelerated, resulting in the difficulty in controlling the particle size of the calcium carbonate particles, a cooling component and a cooling coil are added to the carbonization reactor to take away the heat generated by the carbonization reaction, thereby controlling the temperature of the carbonization reaction system, inhibiting the growth rate of the calcium carbonate particles, and controlling the particle size of the generated calcium carbonate particles to be within the nanometer range; in order to utilize the characteristics of nanoparticles with large surface tension and easy agglomeration of nanoparticles, they are sent to a venturi tube for heating and then cooled after carbonization to fully agglomerate them. In view of the problem that the conventional light calcium carbonate dehydration drum drying-air cannon dispersion drying process easily causes particle compaction and difficulty in dispersion, the nano calcium carbonate particle slurry is directly dried by spray drying, which utilizes the agglomeration characteristics and ensures the dispersibility of the particles.
[0017] According to a second aspect of the present invention, the present invention provides a method for preparing spherical calcium carbonate, comprising the following steps: S1. Preparation of calcium hydroxide slurry Mix quicklime powder and water to carry out digestion reaction. After the reaction is completed, let it stand for aging, filter and remove impurities to obtain calcium hydroxide slurry.
[0018] In this step, the quicklime is ground and passed through a 1000-mesh sieve, and the sieved powder is collected to obtain quicklime powder.
[0019] In this step, the mass ratio of quicklime powder to water is 1:4-8. In some embodiments of the present invention, for example, 1:4, 1:5, 1:6, 1:7, 1:8 can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0020] In this step, the temperature of the digestion reaction is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, and 80°C can be selected; the time of the digestion reaction is 90-180min, for example, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, and 180min can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0021] In this step, the standing aging time is 12-24 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours can be selected (but not limited to the listed values, other values not listed in the numerical range are also applicable).
[0022] In this step, filter with a 200-mesh standard sieve to remove impurities.
[0023] S2. Preparation of calcium carbonate slurry Carbon dioxide gas is introduced into the calcium hydroxide slurry. When the conductivity of the reaction system drops to 3-5 mS / cm, the introduction of carbon dioxide gas is stopped, a crystal form control agent is added thereto, and carbon dioxide gas is continued to be introduced for reaction until the pH of the reaction system is ≤7.0 to obtain a calcium carbonate slurry.
[0024] In this step, the flow rate of carbon dioxide gas is 20-30m 3 / h, for example, you can choose 20m 3 / h、21m 3 / h、22m 3 / h、23m 3 / h、24m 3 / h、25m 3 / h、26m 3 / h、27m 3 / h、28m 3 / h、29m 3 / h、30m 3 / h (but not limited to the listed values, other values not listed in the numerical range are also applicable).
[0025] In this step, the volume ratio of the calcium hydroxide slurry and the crystal form control agent is 1L:10-20mL, for example, 1L:10mL, 1L:12mL, 1L:14mL, 1L:16mL, 1L:18mL, 1L:20mL can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Specifically, the preparation method of the crystal form control agent is as follows: (1) dissolving chitosan in an acetic acid solution, adding sodium periodate thereto, stirring the mixture under a nitrogen atmosphere to react, then adding ethylene glycol to terminate the reaction, concentrating the product by rotary evaporation, dialyzing it, and then freeze-drying it to obtain aldehyded chitosan; (2) dissolving the aldehyde-modified chitosan in an organic solvent, then adding an oxidant, sodium hypochlorite, and stirring to react. After the reaction is completed, the product is concentrated by rotary evaporation, dialyzed, and then freeze-dried to obtain carboxylated chitosan; (3) Dissolve the carboxylated chitosan in water to prepare an aqueous solution, thereby obtaining a crystal form control agent.
[0027] More specifically, in step (1), the mass ratio of chitosan to sodium periodate is 5-10:4-8, for example, 5:4, 5:5, 5:6, 5:7, 5:8, 8:4, 8:5, 8:6, 10:4, 10:5, 10:6, 10:7, 10:8 can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0028] More specifically, in step (1), the stirring reaction temperature is 4-8°C, for example, 4°C, 5°C, 6°C, 7°C, 8°C, and the stirring reaction time is 12-24h, for example, 12h, 15h, 18h, 21h, 24h (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0029] More specifically, in step (1), the specific operation process of dialysis is: first dialyze in a saturated saline solution for 6 hours, and then dialyze in deionized water for 6 hours to remove impurities.
[0030] More specifically, in step (2), the mass ratio of formaldehyded chitosan to sodium hypochlorite is 5-10:8-12, for example, 5:8, 5:10, 5:12, 8:8, 8:10, 8:12, 10:12, 10:8 can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0031] More specifically, in step (2), the stirring reaction time is 12-18 h, for example, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0032] More specifically, in step (2), the specific operation process of dialysis is: first dialyze in a saturated saline solution for 6 hours, and then dialyze in deionized water for 6 hours to remove impurities.
[0033] More specifically, in step (3), the mass fraction of carboxylated chitosan in the aqueous solution is 10-20%, for example, 10%, 12%, 14%, 15%, 18%, 20% (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0034] S3. Preparation of spherical calcium carbonate Maleic anhydride and pyridine, a catalyst for esterification reaction, are added to the calcium carbonate slurry, and the esterification reaction is carried out at 50-60° C. for 2-3 hours. After the reaction is completed, the product is filtered, dehydrated, dried, and crushed to obtain spherical calcium carbonate.
[0035] In this step, based on the mass of carboxylated chitosan, the amount of maleic anhydride added is 20-40%, for example, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% can be selected; the amount of pyridine added is 1-2%, for example, 1%, 1.2%, 1.5%, 1.8%, 2% can be selected (but not limited to the listed values, other values not listed within the numerical range are also applicable).
[0036] According to a third aspect of the present invention, the present invention provides spherical calcium carbonate prepared by the above-mentioned preparation method.
[0037] According to a fourth aspect of the present invention, the present invention also provides the use of the spherical calcium carbonate in the preparation of polyethylene film.
[0038] Compared with the prior art, the present invention has the following beneficial effects: (1) By adjusting different process conditions, nano-CaCO3 products with different morphological characteristics and special functions can be prepared, thereby improving its application performance in the industry, obtaining stable calcite structured spherical calcium carbonate particles and reducing the proportion of calcite particles. No surface treatment or surface coating is required, but spray drying is directly performed by a spray drying method, and spherical nano-calcium carbonate particles are generated by utilizing the characteristics of large surface tension of nano-particles and easy hard agglomeration.
[0039] (2) The present invention first performs an aldehyde modification treatment on chitosan, and then performs a carboxyl modification treatment, thereby improving the water solubility of chitosan. Then, carboxylated chitosan is used as a crystal control agent. Carboxylated chitosan has a polymer chain structure, and the carboxyl group has a stronger adsorption capacity for calcium ions than the hydroxyl group. Calcium ions are easy to form a covalent structure with the carboxyl group on the molecular chain of the crystal control agent, so that a large number of calcium ions are enriched near the molecular chain. At the same time, the positively charged calcium ions will attract nearby carbonate ions, so that calcium carbonate forms a large number of calcium carbonate crystal nuclei in the microenvironment of the polymer chain. The crystal control agent with a large number of calcium carbonate crystal nuclei can further adsorb to the surface of calcium carbonate particles, inhibit the growth of particles in a linear direction, and prevent calcium carbonate from forming large agglomerated particles, thereby obtaining regular spherical calcium carbonate. When it is used as a filler for PE resin film, the mechanical properties of the film can be significantly improved.
[0040] (3) The present invention performs esterification treatment on the remaining hydroxyl groups on the chitosan molecular chain and grafts maleic anhydride hydrolyzate to reduce the surface energy of calcium carbonate, while improving the compatibility of calcium carbonate powder and PE resin, further improving the mechanical properties of PE resin film. When the spherical calcium carbonate prepared by the present invention is used as a filler for PE resin film, the filling amount can reach 50%, while maintaining good tensile strength.
[0041] (4) One aspect of the present invention utilizes the characteristics of agglomeration, introduces a venturi tube, and controls the temperature and pH value during spray drying to achieve the production of spherical calcium carbonate particles with a reduced proportion of calcite crystals. Another aspect is to achieve the production of spherical calcium carbonate particles with a reduced proportion of calcite crystals by controlling the crystal form. Regardless of which method is used, whether it is to utilize the agglomeration characteristics or to prevent large agglomerations, spherical calcium carbonate particles can be perfectly formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The electron microscope image at a scale of 100 micrometers is prepared to illustrate the method for preparing spherical calcium carbonate particles according to Example 1 of the present invention.
[0043] Figure 2 The electron microscope image at a scale of 80 microns is prepared to illustrate the method for preparing spherical calcium carbonate particles according to Example 2 of the present invention. DETAILED DESCRIPTION
[0044] The method for preparing spherical calcium carbonate particles of the present invention will be described in detail below with reference to the accompanying drawings in combination with specific embodiments. Those skilled in the art will appreciate that the description is exemplary and the present invention is not limited to the specific embodiments.
[0045] Example 1 A method for preparing spherical calcium carbonate particles by using a spray drying process, wherein a raw material slurry is pumped into a carbonization reactor from a feed port, and a stirring motor drives a stirring rod with a paddle to stir, and carbon dioxide enters the carbonization reactor through a rotating ultrasonic atomizing nozzle via the stirring rod to react with the raw material slurry in a carbonization reaction; the heat generated by the carbonization reaction is cooled by a coolant through a cooling coil and a cooling component for heat exchange, and the coolant absorbs the heat of the carbonization reaction system and enters a coolant storage tank, and is cooled by a refrigerator and then returns to the coolant storage tank, and is pumped into the cooling coil and the cooling component by a freezing liquid pump again for heat exchange of the carbonization reaction system; the temperature and pH value of the slurry in the carbonization tank are monitored by a temperature sensor and a pH test box, and when the pH value drops to a certain value, the reaction is stopped, and the slurry is connected to a venturi tube treatment device after being stirred for a period of time. In the spray drying device, the clinker slurry is pumped out from the cooling device in the venturi tube processing device by the clinker slurry pump and enters the spray drying generating tower through the spray nozzle. The air is sucked into the spray drying generating tower through the air intake fan and the air heating device. The dried nano calcium carbonate material is discharged from the material discharge port at the bottom of the spray drying tower. The carbon dioxide gas is separated from the material by the separator and then discharged into the atmosphere through the fan and dust collector. The spray drying method is used to directly spray dry, and the characteristics of nano particles with large surface tension and easy to produce hard agglomeration are utilized to generate nano particles such as Figure 1 Spherical nano calcium carbonate particles are shown.
[0046] Example 2 A method for preparing spherical calcium carbonate comprises the following steps: S1. The quicklime powder was passed through a 1000-mesh sieve, and then the quicklime powder and water were mixed in a mass ratio of 1:5, followed by a digestion reaction at 60°C for 180 minutes. After the reaction was completed, the mixture was allowed to stand for 12 hours, and filtered through a 200-mesh standard sieve to remove impurities to obtain a calcium hydroxide slurry.
[0047] S2, carbon dioxide gas is introduced into the calcium hydroxide slurry, and the flow rate of carbon dioxide gas is 25m3 / h. When the conductivity of the reaction system drops to 3mS / cm, the introduction of carbon dioxide gas is stopped, and a crystal form control agent is added thereto. The volume ratio of calcium hydroxide slurry to the crystal form control agent is 1L:150mL. Carbon dioxide gas is continued to be introduced for reaction, and the flow rate of carbon dioxide gas is 25m3 / h. 3 / h, until the pH of the reaction system is ≤7.0, to obtain a calcium carbonate slurry; Wherein, the preparation method of the crystal form control agent is as follows: (1) 5 g of chitosan was dissolved in 100 mL of 10 wt% acetic acid solution, 4 g of sodium periodate was added thereto, and the mixture was stirred and reacted at 5°C under nitrogen atmosphere for 12 h. Then, 5 mL of ethylene glycol was added to terminate the reaction. The product was concentrated by rotary evaporation and then dialyzed. The specific operation process of dialysis was as follows: first, dialyzed in a saturated saline solution for 6 h, then dialyzed in deionized water for 6 h to remove impurities, and then freeze-dried to obtain aldehyded chitosan; (2) Dissolve 5 g of aldehyded chitosan in 100 mL of tetrahydrofuran, then add 5 g of oxidant sodium hypochlorite, and stir at room temperature for 12 h. After the reaction is completed, the product is concentrated by rotary evaporation and then dialyzed. The specific operation process of dialysis is: first dialyze in a saturated saline solution for 6 h, then dialyze in deionized water for 6 h to remove impurities, and then freeze-dry to obtain carboxylated chitosan; (3) Dissolve 10 g of carboxylated chitosan in 100 g of water to prepare an aqueous solution, thereby obtaining a crystal form control agent.
[0048] S3, add maleic anhydride and esterification catalyst pyridine to the calcium carbonate slurry, based on the mass of the carboxylated chitosan, the amount of maleic anhydride added is 30% of the mass of the carboxylated chitosan, and the amount of pyridine added is 1% of the mass of the carboxylated chitosan, and the esterification reaction is carried out at 50°C for 3h. After the reaction is completed, the product is filtered, dehydrated, dried, and crushed to obtain Figure 2 Spherical calcium carbonate particles shown.
[0049] Comparative Example 1 A method for preparing calcium carbonate comprises the following steps: S1. The quicklime powder was passed through a 1000-mesh sieve, and then the quicklime powder and water were mixed in a mass ratio of 1:5, followed by a digestion reaction at 60°C for 180 minutes. After the reaction was completed, the mixture was allowed to stand for 12 hours, and filtered through a 200-mesh standard sieve to remove impurities to obtain a calcium hydroxide slurry.
[0050] S2, into the calcium hydroxide slurry, carbon dioxide gas is passed, the flow rate of carbon dioxide gas is 25m3 / h, when the conductivity of the reaction system is reduced to 3mS / cm, the carbon dioxide gas is stopped, and a crystal form controller is added thereto, the volume ratio of the calcium hydroxide slurry and the crystal form controller is 1L:150mL, and carbon dioxide gas is continued to be passed to react, and the flow rate of carbon dioxide gas is 25m3 / h, until the pH of the reaction system is ≤7.0, to obtain a calcium carbonate slurry; The preparation method of the crystal form control agent is as follows: 10 g of soluble corn starch is dissolved in 100 g of water to prepare an aqueous solution, thereby obtaining the crystal form control agent.
[0051] S3. Add maleic anhydride and esterification reaction catalyst pyridine to the calcium carbonate slurry. Based on the mass of carboxylated chitosan, the amount of maleic anhydride added is 30% of the mass of carboxylated chitosan, and the amount of pyridine added is 1% of the mass of carboxylated chitosan. The esterification reaction is carried out at 50°C for 3 hours. After the reaction is completed, the product is filtered, dehydrated, dried, and crushed to obtain calcium carbonate.
[0052] Compared with Example 2, Comparative Example 1 uses soluble corn starch instead of carboxylated chitosan.
[0053] Comparative Example 2 A method for preparing calcium carbonate comprises the following steps: S1. The quicklime powder was passed through a 1000-mesh sieve, and then the quicklime powder and water were mixed in a mass ratio of 1:5, followed by a digestion reaction at 60°C for 180 minutes. After the reaction was completed, the mixture was allowed to stand for 12 hours, and filtered through a 200-mesh standard sieve to remove impurities to obtain a calcium hydroxide slurry.
[0054] S2, into the calcium hydroxide slurry, carbon dioxide gas is passed, the flow rate of carbon dioxide gas is 25m3 / h, when the conductivity of the reaction system is reduced to 3mS / cm, the carbon dioxide gas is stopped, and a crystal form controller is added thereto, the volume ratio of the calcium hydroxide slurry and the crystal form controller is 1L:150mL, and carbon dioxide gas is continued to be passed to react, and the flow rate of carbon dioxide gas is 25m3 / h, until the pH of the reaction system is ≤7.0, to obtain a calcium carbonate slurry; The preparation method of the crystal form control agent is as follows: 10 g of carboxymethyl chitosan is dissolved in 100 g of water to prepare an aqueous solution, thereby obtaining the crystal form control agent.
[0055] S3. Add maleic anhydride and esterification reaction catalyst pyridine to the calcium carbonate slurry. Based on the mass of carboxylated chitosan, the amount of maleic anhydride added is 30% of the mass of carboxylated chitosan, and the amount of pyridine added is 1% of the mass of carboxylated chitosan. The esterification reaction is carried out at 50°C for 3 hours. After the reaction is completed, the product is filtered, dehydrated, dried, and crushed to obtain calcium carbonate.
[0056] Compared with Example 2, Comparative Example 2 uses carboxymethyl chitosan instead of carboxylated chitosan.
[0057] Comparative Example 3 A method for preparing calcium carbonate comprises the following steps: S1. The quicklime powder was passed through a 1000-mesh sieve, and then the quicklime powder and water were mixed in a mass ratio of 1:5, followed by a digestion reaction at 60°C for 180 minutes. After the reaction was completed, the mixture was allowed to stand for 12 hours, and filtered through a 200-mesh standard sieve to remove impurities to obtain a calcium hydroxide slurry.
[0058] S2, into the calcium hydroxide slurry, carbon dioxide gas is passed, the flow rate of carbon dioxide gas is 25m3 / h, when the conductivity of the reaction system is reduced to 3mS / cm, the carbon dioxide gas is stopped, and a crystal form controller is added thereto, the volume ratio of the calcium hydroxide slurry and the crystal form controller is 1L:150mL, and carbon dioxide gas is continued to be passed to react, and the flow rate of carbon dioxide gas is 25m3 / h, until the pH of the reaction system is ≤7.0, to obtain a calcium carbonate slurry; Wherein, the preparation method of the crystal form control agent is as follows: (1) 5 g of chitosan was dissolved in 100 mL of 10 wt% acetic acid solution, 4 g of sodium periodate was added thereto, and the mixture was stirred and reacted at 5°C under nitrogen atmosphere for 12 h. Then, 5 mL of ethylene glycol was added to terminate the reaction. The product was concentrated by rotary evaporation and then dialyzed. The specific operation process of dialysis was as follows: first, dialyzed in a saturated saline solution for 6 h, then dialyzed in deionized water for 6 h to remove impurities, and then freeze-dried to obtain aldehyded chitosan; (2) Dissolve 5 g of aldehyded chitosan in 100 mL of tetrahydrofuran, then add 5 g of oxidant sodium hypochlorite, and stir at room temperature for 12 h. After the reaction is completed, the product is concentrated by rotary evaporation and then dialyzed. The specific operation process of dialysis is: first dialyze in a saturated saline solution for 6 h, then dialyze in deionized water for 6 h to remove impurities, and then freeze-dry to obtain carboxylated chitosan; (3) Dissolve 10 g of carboxylated chitosan in 100 g of water to prepare an aqueous solution, thereby obtaining a crystal form control agent.
[0059] S3. Add maleic anhydride to the calcium carbonate slurry, the amount of maleic anhydride added is 30% of the mass of the carboxylated chitosan based on the mass of the carboxylated chitosan, and stir the reaction at 50° C. for 3 hours. After the reaction is completed, the product is filtered, dehydrated, dried, and crushed to obtain calcium carbonate.
[0060] Compared with Example 2, in Comparative Example 3, no esterification reaction catalyst pyridine was added, and the maleic anhydride hydrolyzate was attached to the surface of calcium carbonate through hydrogen bonding.
[0061] The calcium carbonate in Example 2 and Comparative Examples 1-3 was extruded and granulated according to the formula of 49.5% PE resin (CAS: 9002-88-4) + 50% calcium carbonate + 0.5% polyethylene wax, and then processed by a casting machine to obtain a breathable film, and a 100 mm × 45 mm sample was made for testing, wherein the tensile properties were tested according to the GB / T 1040-2018 method, and the tensile speed was set to 100 mm / min. The test results are shown in Table 1.
[0062] Table 1 Mechanical properties test results
[0063] As can be seen from Table 1, in Comparative Examples 1 and 2, respectively, common crystal form control agents starch and carboxymethyl chitosan are used. When the prepared calcium carbonate is used as a filler, its mechanical properties are not as good as those of Example 2 of the present invention. The reason may be that the polarity of the chitosan molecules can be effectively increased by carboxylation treatment, so that its effectiveness in contact with calcium ions and carbonate ions in the aqueous phase is significantly enhanced; compared with Comparative Example 3, in Example 2 of the present invention, maleic anhydride hydrolyzate is grafted by esterification reaction, which is beneficial to improve the mechanical properties of the PE resin film.
[0064] In summary, the present invention has been described in detail with reference to specific embodiments. One of the embodiments 1 utilizes the characteristics of agglomeration, and by introducing a venturi tube, controls the temperature and pH value during spray drying, and realizes the production of spherical calcium carbonate particles that reduce the proportion of calcite crystal forms. Another embodiment 2 is the production of spherical calcium carbonate particles that reduce the proportion of calcite crystal forms by controlling the crystal form. However, it is obvious that the present invention is not limited to the specific embodiments, and for those skilled in the art, various modifications and improvements can be made to it on the basis of the present invention. Any modification or improvement made without departing from the purpose and spirit of the present invention should fall within the protection scope of the present invention, and the protection scope of the present invention is defined by the attached claims.
Claims
1. A method for preparing spherical calcium carbonate, characterized in that, The steps include: S1, quicklime powder and water are mixed, and digestion reaction is carried out. After the reaction is completed, standing and aging are carried out, and impurities are removed by filtering to obtain calcium hydroxide slurry; S2, introducing carbon dioxide gas into the calcium hydroxide slurry, when the conductivity of the reaction system drops to 3-5mS / cm, stop introducing carbon dioxide gas, add a crystal form control agent thereto, continue to introduce carbon dioxide gas to react until the pH of the reaction system is ≤7.0, to obtain a calcium carbonate slurry; S3, adding maleic anhydride and pyridine, a catalyst for esterification reaction, to the calcium carbonate slurry, and carrying out esterification reaction at 50-60° C. for 2-3 hours. After the reaction is completed, the product is subjected to filter pressing, dehydration, drying, and crushing to obtain spherical calcium carbonate; In step S2, the preparation method of the crystal form control agent is as follows: (1) dissolving chitosan in an acetic acid solution, adding sodium periodate thereto, stirring the mixture under a nitrogen atmosphere to react, then adding ethylene glycol to terminate the reaction, concentrating the product by rotary evaporation, dialyzing it, and then freeze-drying it to obtain aldehyded chitosan; (2) dissolving the aldehyde-modified chitosan in an organic solvent, then adding an oxidant, sodium hypochlorite, and stirring to react. After the reaction is completed, the product is concentrated by rotary evaporation, dialyzed, and then freeze-dried to obtain carboxylated chitosan; (3) Dissolve the carboxylated chitosan in water to prepare an aqueous solution, thereby obtaining a crystal form control agent.
2. The preparation method according to claim 1, characterized in that: In step S3, based on the mass of carboxylated chitosan, the amount of maleic anhydride added is 20-40%, and the amount of pyridine added is 1-2%.
3. as the spherical calcium carbonate prepared by the preparation method as described in any one of claim 1-2.
4. Application of spherical calcium carbonate as claimed in claim 3 in the preparation of polyethylene film.
Citation Information
Patent Citations
Low-alkalinity calcium carbonate and preparation process thereof
CN115558316A
Calcium carbonate-carboxylic acid-chitosan cured product and preparation thereof
JP2000226402A